Curating Scientific Workflows for Biomolecular Nuclear Magnetic Resonance Spectroscopy - Douglas Heintz; Michael R Gryk (International Journal of Digital Curation, 2019)
This paper describes our recent and ongoing efforts to enhance the curation of scientific workflows to improve reproducibility and reusability of biomolecular nuclear magnetic resonance (bioNMR) data. Our efforts have focused on both developing a workflow management system, called CONNJUR Workflow Builder (CWB), as well as refactoring our workflow data model to make use of the PREMIS model for digital preservation. This revised workflow management system will be available through the NMRbox cloud-computing platform for bioNMR. In addition, we are implementing a new file structure which bundles the original binary data files along with PREMIS XML records describing the provenance of the data. These are packaged together using a standardized file archive utility. In this manner, the provenance and data curation information is maintained together along with the scientific data. The benefits and limitations of these approaches, as well as future directions, are discussed in this paper.